Gallery Game: Smartphone-based assessment of long-term memory in adults at risk of Alzheimer's disease. Issue 4 (20th April 2020) - Lancaster, Claire; Koychev, Ivan; Blane, Jasmine; Chinner, Amy; Chatham, Christopher; Taylor, Kirsten; Hinds, Chris
ABSTRACT: Introduction : Gallery Game, deployed within the Mezurio smartphone app, targets the processes of episodic memory hypothesized to be first vulnerable to neurofibrillary tau-related degeneration in Alzheimer's Disease, prioritizing both perirhinal and entorhinal cortex/hippocampal demands. Methods : Thirty-five healthy adults (aged 40–59 years), biased toward those at elevated familial risk of dementia, completed daily Gallery Game tasks for a month. Assessments consisted of cross-modal paired-associate learning, with subsequent tests of recognition and free recall following delays ranging from one to 13 days. Results : Retention intervals of at least three days were needed to evidence significant forgetting at both recognition and paired-associate recall test. The association between Gallery Game outcomes and established in-clinic memory assessments were small but numerically in the anticipated direction. In addition, there was preliminary support for utilizing the perirhinal-dependent pattern of semantic false alarms during object recognition as a marker of early impairment. Conclusions : These results support the need for tests of longer-term memory to sensitively record behavioral differences in adults with no diagnosis of cognitive impairment. Aggregate behavioral outcomes promote Gallery Game's utility as a digital assessment of episodic memory, aligning with established theoretical models of object memory and showing small yet uniform associations with existing in-clinic tests. Initial support for the discriminatory value of perirhinal-targeted outcomes justifies ongoing large-sample validation against traditional biomarkers of Alzheimer's disease.